Education and technology key issues and debates - Selwyn, Neil 1973- (Bloomsbury, 2017)
"Will technology replace the school and university? Will technology replace the teacher? What do we really know about technology and learning? Does technology make education more individualized? What does the future hold for technology and education? What can be learnt from the history of technology use in education? In a thoroughly revised edition of this successful book, Neil Selwyn takes a critical look at some of the major current debates and controversies concerning digital technologies and education. Focusing on the social as well as the technical aspects of these issues, Selwyn addresses fundamental but often unvoiced questions about education and technology. Over the course of eight chapters, the book gives careful thought to the people, practices, processes and structures behind the rapidly increasing use of technologies in education, with an emphasis on the implications of digital technologies for individuals and institutions. The book focuses attention on the connections between recent technology developments and broader changes in education practice, education policy and education theory over the past 10 years. It also challenges us to reflect on future directions and controversies for education in the (post)digital age. Expanded study questions, annotated further reading and a new glossary of key terms are included to support readers. An updated companion website links to case study examples, two bonus chapters and much more for students and lecturers."...